T4 Safety and expression of a single dose of lipid-mediated CFTR gene therapy to the upper and lower airways of patients with Cystic Fibrosis. (2nd December 2011) - Davies, G; Davies, J C; Gill, D R; Hyde, S C; Boyd, C; Innes, J A; Porteous, D J; Cheng, S H; Scheule, R K; Higgins, T; Griesenbach, U; Alton, E W F W
Abstract : Introduction and Objectives: We undertook a clinical trial of non-viral CFTR gene therapy assessing safety, dose and transgene expression in preparation for a Multi-dose trial (MDT) designed to assess clinical efficacy. Methods: A single nebulised and/or nasal dose of plasmid CFTR (pGM169)/GL67A was delivered to patients aged =16 years with a baseline FEV1 >60% predicted. Clinical and laboratory parameters were measured at intervals until day 28. A cohort of patients also underwent pre- and post-dosing (day 6 or 14) bronchoscopies for functional (airway potential difference (PD)) and molecular (QRT-PCR) evidence of vector-specific CFTR expression. Patients receiving a nasal dose underwent brushings for QRT-PCR and serial nasal PD measurements. Results: 35 patients received a nebulised dose of 20 ml (n=17), 10 ml (n=10) or 5 ml (n=8). A short-lived, dose-related drop in FEV1 was observed over the next 6 h (mean [SD]: 20 ml 25.7 [10.2]%; 10 ml 17.7 [9.9]%; 5 ml 13.0 [4.4]% of baseline). Subjects also experienced a systemic inflammatory response which was similarly dose-related and generally limited to the first 24–48 h post-dosing. A cohort of 6 patients (4@10 ml; 2@5 ml) received 4 g paracetamol over an 18-h period post-dosing; none of these patients developed a fever. Intriguingly, these subjects also appeared to have reduced systemic inflammatory responses. Molecular (mRNA) evidence of gene transfer was observed in some individuals from upper or lower airway brushings. On lower airway PD measurement, the majority of patients showed an increase towards non-CF values after nebulised gene therapy. 19 patients received a 2 ml nasal dose and 11 (58%) had some response in chloride secretion on nasal PD. In the two most positive individuals, responses were within the normal (non-CF) range and persisted to days 63 and 91, respectively. Conclusions: We consider the side effects after 20 ml nebulised dose excessive for repeated application. Those at 10 and 5 ml were more acceptable. Gene expression was confirmed in some patients, and restoration of CFTR function to the non-CF range has been observed out to 13 weeks following a single nasal dose. These data support progression of this agent to MDT.